HEAT TRANSFER MODULE, HEAT PIPE, AND MANUFACTURING METHOD OF HEAT PIPE - HUANG YU-NIEN; CHENG CHENG-YU (2014)
A heat pipe includes a flat tube, a first capillary structure, a second capillary structure, and a capillary structure block. The flat tube has flat portions, a first arc portion and a second arc portion. The first arc portion and the second arc portion are respectively connected to the opposite sides of the flat portions. The first capillary structure is accommodated in the flat tube and is in contact with the first arc portion. The second capillary structure is accommodated in the flat tube, and is in contact with the second arc portion. The first and second capillary structures are spaced apart from each other, and define a gas flowing chamber therebetween. The capillary structure block is disposed on a partial area of the gas flowing chamber, and is in contact with the flat portions, the first and second capillary structures.